Shura in the View of Muhammad Rasyid Ridho - Muhamad Fajar Pramono; Taufiqurrohman (al-Afkar, Journal For Islamic Studies, 2025)
In the discourse of Islamic political thought, spanning both pre-modern and contemporary eras, the concept of "shura" (consultation) holds significant importance among Muslim scholars, particularly Islamic political thinkers. One prominent figure in this domain during the modern era is Sayyid Muhammad Rashid Ridha. His noteworthy contributions to political thought are encapsulated in his seminal work, "Khilafot aw al-Imamat al-Uzma." His ideas are regarded as insightful and remain relevant in current political discussions. Rida contends that "shura" should serve as the cornerstone in the system of Islamic governance.